FEASIBILITY EVALUATION OF THE RELATIONSHIP BETWEEN BCWS, BCWP AND ACWP IN ROAD CONSTRUCTION PROJECT - Massayu Sekar Bawana; I Nyoman Dita Pahang Putra; Elok Dewi Widowati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The development of adequate infrastructure, such as roads, bridges, and other public facilities, play a vital role in driving national economic growth. Infrastructure projects require careful planning and controlled execution to ensure effective and efficient outcomes. This study focus on addressing the common issues of delays and cost overruns that frequently occur during project implementation. The objective is to analyze the alignment between planned and actual project performance. Using a quantitative methods, this research integrated the Earned Value Method (EVM) to assess project performance. The results indicate that, between weeks 26 and 39, the project generated performance that was both ahead of schedule and below budget. This is evidenced by positive values in both schedule and cost variance (SV and CV), along with the Schedule and Cost Performance Index (SPI and CPI) values exceeding 1. However in week 40, a decrease in schedule performance was observed, leading to a slight project delay. The project’s estimated overall cost is IDR 116.8 billion, representing a decrease from the initial budget allocation, with an estimated delay is only around 18 days.